2024
DOI: 10.1111/liv.15847
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid function, adipokines and mitokines in metabolic dysfunction‐associated steatohepatitis: A multi‐centre biopsy‐based observational study

Matina Kouvari,
Laura Valenzuela‐Vallejo,
Evangelos Axarloglou
et al.

Abstract: Background and AimsThyroid axis is currently under investigation as a therapeutic target in metabolic dysfunction‐associated steatotic liver disease (MASLD). Thyroid function was examined herein in the full spectrum of disease.MethodsSubjects were recruited and had liver biopsies in two Gastroenterology‐Hepatology Clinics (Greece and Australia) and one Bariatric‐Metabolic Surgery Clinic (Italy). The main working sample was n = 677 subjects with MASLD after excluding subjects with abnormal free thyroxine levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 69 publications
(178 reference statements)
0
1
0
Order By: Relevance
“…In parallel, strong epidemiological evidence has indicated that hypothyroidism is also tightly associated with the development and fibrotic progression of NAFLD and NASH [19][20][21][22]. This association has recently been found to be sex-specific and mediated by adipokines/mitokines [23].…”
Section: What Has Nash To Do With Thyroid?mentioning
confidence: 97%
“…In parallel, strong epidemiological evidence has indicated that hypothyroidism is also tightly associated with the development and fibrotic progression of NAFLD and NASH [19][20][21][22]. This association has recently been found to be sex-specific and mediated by adipokines/mitokines [23].…”
Section: What Has Nash To Do With Thyroid?mentioning
confidence: 97%